The study of the environmental efficiency of energy production from various sources of raw materials - Gryznova, Ekaterina; Davydov, Vadim; Grebenikova, Nadya; Puz'ko, Danila; Karakotov, Salys; Nadykta, Vladimir; Ivanov, Dmitry; Bykov, Valeriy (IOP conference series. Earth and environmental science, 2019)
The article substantiates the need to assess the energy efficiency of energy production from various types of fuel. The most significant indicators for assessing the environmental efficiency of the use of fuel for electricity production are established. A methodology for assessing the environmental efficiency of using various methods for the production of electricity is proposed. Research results are presented.